Specifications for Planting Trees and Shrubs in the Southeastern U.S. - Edward F. Gilman (EDIS)
This document is ENH856, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date March 12, 2002.